The membrane free sonoelectroanalytical determination of trace levels of lead and cadmium in human saliva. - Hardcastle, J; West, C; Compton, R (2002)
In this paper, square wave anodic stripping voltammetry (SWASV), synergistically coupled with an ultrasonically enhanced preconcentration step has been shown to yield a quantitative determination of lead and cadmium in human saliva at a membrane free in situ plated mercury thin film glassy carbon electrode. The sensitivity was facilitated by acoustic streaming which promoted efficient mass transport to the electrode thus reducing sampling times. Cavitation was responsible for cleaning and activating the electrode surface, this was essential in order to obtain a reproducible and representative signal. In silent conditions electrode fouling leading to fluctuations in the baseline current and signal depression, precluded accurate quantitative analyses. The results presented herein provide an extension to the proof of concept given in the authors' earlier work, with the analysis of lead in human saliva as opposed to artificial saliva reported. We also address the hitherto unreported detection and determination of cadmium in this medium. Results for both were independently verified by inductively coupled plasma-mass spectroscopy (ICP-MS). Close agreement between lead concentration determined by sono-SWASV and independent and blind ICP-MS is reported for human saliva samples having a total lead content of 0.92 microg L(-1) and 5 microg L(-1) with a detection limit of 0.5 microg L(-1). Microaddition calibration data for cadmium additions of 0.0125 microg L(-1) to samples spiked with 2.5 microg L(-1) and 5.0 microg L(-1) (reflecting levels in workers occupationally exposed) exhibited close agreement with the known total cadmium in the samples. A detection limit of 1 microg L(-1) cadmium in saliva has been established.